The Effects of Aerobic Exercise on Functional Capacity of Geriatric Chronic Heart Failure Patients - Muhammad Khalimur Rouf; Irsad Andi Arso; I Dewa Putu Pramantara (Acta Interna The Journal of Internal Medicine, 2016)
Background: Chronic heart failure, a condition predominantly affecting the elderly, is a major clinical burden and cause death in admission patients especially the elderly population.  The focus of cardiac rehabilitation recently is exercise used as one of the modality of therapy designed for stable heart failure patients.  Exercise is recommended as one of modality in management of heart failure to improve prognosis, increase physical activity tolerance and quality of life of heart failure patients. Aim: The objective of this study is to understand is aerobic exercise program can improve functional capacity in geriatric heart failure patients. Methods: The design of this study is randomized controlled trial.  Twenty subjects were cardiology outpatient clinic at Dr Sardjito hospital men and women with chronic heart failure functional class I-II of NYHA age > 60 years and agreed to be included to the study.  Subjects were divided into two group randomly, which were the exercise group (10 subjects) and the control group (10 subjects).  To compare the functional capacity of both groups, t-test independent is used with condition of normal data range and Mann Whitney test is used if abnormal data range is found. The level of significance was set at p<0,05 with confidence interval 95% Result : Comparison of the mean increase in the six minute walk test distance between aerobic exercise group 107.9 ± 22.153 meters compared with the control group 21.3 ± 16.166 was significantly better in the aerobic exercise group (p <0.001) Conclusion : Aerobic exercise can improve the functional capacity of patients with chronic heart failure in the elderly. Keyword: chronic heart failure, elderly, aerobic exercise, functional capacity.